Our Struggles With Resilience: Using Political Ecology to Strengthen the Concept of Resilience in Empirical Field Research and Critical Policy Analysis - Schilling, Janpeter; Haider-Nash, Sarah; Hüttenrauch , Lissy (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
The concept of resilience is omnipresent in scholarship and policymaking on climate change. Yet, resilience has major shortcomings that leave us—a human geographer primarily relying on empirical field research and a political scientist working with critical policy analysis—conflicted about the concept. On the one hand, it is part of our disciplines’ lingua franca, while on the other hand, the conceptual critiques are both common and persuasive. In this article, we share our perspective on resilience, guided by the following question: What challenges do we face in applying the concept of resilience in empirical field research and critical policy analysis, and how can we address them? We answer this question based on climate impacts in, and policy perspectives on, Kenya. We do not resolve all the challenges of working with resilience in social sciences research, but building upon the existing literature identifying the strengths and shortcomings of resilience and our own experiences with the concept, we put forward one potential path that uses political ecology to overcome some of resilience’s shortcomings while maintaining its utility for our research. These insights are likely to be relevant and useful for other researchers, policymakers, and practitioners.